Nitrogen addition reduces soil respiration but increases the relative contribution of heterotrophic component in an alpine meadow. (28th August 2019) - Wang, Jinsong; Song, Bing; Ma, Fangfang; Tian, Dashuan; Li, Yong; Yan, Tao; Quan, Quan; Zhang, Fangyue; Li, Zhaolei; Wang, Bingxue; Gao, Qiang; Chen, Weinan; et al.
Abstract: Disentangling the relative response sensitivity of soil autotrophic ( R a ) and heterotrophic respiration ( R h ) to nitrogen (N) enrichment is pivotal for evaluating soil carbon (C) storage and stability in the scenario of intensified N deposition. However, the mechanisms underlying differential sensitivities of R a and R h and relative contribution of R h to soil respiration ( R s ) with increasing N deposition remain elusive. A manipulative field experiment with multi‐level N addition rates was conducted over 3 years (2015–2017) in an alpine meadow to explore the relative impact of N enrichment on R a and R h and the response of R h / R s ratio to the gradient of N addition. Soil respiration components had different sensitivities to N enrichment, with R a decreasing more than R h, leading to a higher R h / R s ratio as a function of increasing N addition rates. R a and R h decreased nonlinearly as N addition rates increased, with a critical load of 8 g N m −2 year −1 above which N enrichment significantly inhibited them. R a and R h were controlled by different abiotic and biotic factors, and the regulation of controlling factors on soil respiration components varied over time. N‐induced reduction in the relative abundance of forb significantly affected R a, and this effect was mainly evident in the second and third years. Nitrogen enrichment significantly changed R h in the third year, and the decreased R h under high doses of N addition could be attributed to the changes in microbial biomass C, soil substrate quality and microbial composition. Our study highlights the leading role of R a in regulating R s responses to N enrichment and the enhancement of R h / R s ratio with increasing N addition. We also emphasize that N‐induced shifts in plant community composition play a vital role in regulating R a instead of R h . The changing drivers of R a and R h with time suggests that long‐term experiments with multiple levels of N addition are further needed to test the nonlinear responses and underlying mechanisms of soil respiration components in face to aggravating N deposition. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.